Water Kinetic Treatment as Standard Post Partum Care to Overcome Delayed on Set Muscle Sorness (DOMS) - Bambang Trisnowiyanto; Runjati Runjati; Emy Suryani (JURNAL KEBIDANAN, 2019)
The process of labor through which the mother gives rise to the muscles due to the process of contraction, pain, and straining at the time of labor. Labor process cause muscle tension. Tension in the muscles that causes pain that requires the mother's help after delivery. Delayed onset muscle soreness DOMS is discomfort and pain in the muscles that result in a decrease in muscle strength, decreased joint motion (LGS) and damage to muscle tissue. The purpose of this study was to determine the effect of giving Water Kinetic Treatment to the reduction of DOMS in gastrocnemius muscle. This study was a two-group pre and post-test design that aims to find out how much influence the Water Kinetic Treatment has on reducing DOMS in normal postpartum, Water Kinetic Treatment is given 12 hours after normal parturition. Respondents were selected from the first postpartum gravida maternal patient with no complications after the normal parturition at salatiga Hospital which were for each group 6 mothers. Mothers wa given treatment for 4 days. Data were analyzed using paired t-test and independent t-test. Provision of Water Kinetic Treatment 12 hours after normal parturition did not affect the reduction in DOMS before and after the intervention (p 0.05), but there was a significant influence between the group given water kinetic treatment therapy and the group that was not given to decrease DOMS (p 0.05). There was a significant effect on the group given water kinetic treatment compared to the group not treated for a decrease in pain scale and increased muscle strength for 4 days of treatment.